2020
DOI: 10.3390/cancers12061507
|View full text |Cite
|
Sign up to set email alerts
|

Small Non-Coding RNA Profiling in Plasma Extracellular Vesicles of Bladder Cancer Patients by Next-Generation Sequencing: Expression Levels of miR-126-3p and piR-5936 Increase with Higher Histologic Grades

Abstract: Bladder cancer (BC) is the tenth most frequent cancer worldwide. Due to the need for recurrent cystoscopies and the lack of non-invasive biomarkers, BC is associated with a high management burden. In this respect, small non-coding RNAs (sncRNAs) have been investigated in urine as possible biomarkers for BC, but in plasma their potential has not yet been defined. The expression levels of sncRNAs contained in plasma extracellular vesicles (EVs) from 47 men with BC and 46 healthy controls were assessed by next-ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
46
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 54 publications
2
46
1
Order By: Relevance
“…Only miR-126-3p was significantly upregulated in bladder cancers with respect to controls in both plasma EVs and urine. Although in this study authors did not specifically evaluate urinary EVs-miRNAs, but urinary cell-free miRNAs, results suggest caution in translating plasma results to urinary miRNA profiles [104]. Similar results were obtained in type 2 diabetes mellitus by Park et al that first compared various isolation methods and then evaluated the correlations of EVs miRNA between urine and serum samples.…”
Section: Bladder Cancersupporting
confidence: 58%
“…Only miR-126-3p was significantly upregulated in bladder cancers with respect to controls in both plasma EVs and urine. Although in this study authors did not specifically evaluate urinary EVs-miRNAs, but urinary cell-free miRNAs, results suggest caution in translating plasma results to urinary miRNA profiles [104]. Similar results were obtained in type 2 diabetes mellitus by Park et al that first compared various isolation methods and then evaluated the correlations of EVs miRNA between urine and serum samples.…”
Section: Bladder Cancersupporting
confidence: 58%
“…[ 22 ] The loading of molecules into the exosomes is a selective process that is not yet completely clarified. [ 23 ] Exosomes are stable carriers of enriched genetic material and proteins from their cells of origin, thereby holding great promise as biomarker for identifying early stage tumors. This analyte is systematically detectable in the blood, urine, saliva, and other biological fluids of patients with different cancer types.…”
Section: Circulating Tumor Biomarkersmentioning
confidence: 99%
“…Furthermore, some authors have shown that nucleic acids, specially DNA, might not be part of the exosomal cargo, or that other vesicles such as large EVs (oncosomes) bodies hold most of the DNA. [ 14–38 ] As more robust methods appear, these issues will be clarified in a near future. Finally, the potential of exosomes is huge, not only for their use as biomarkers, but also because these EVs can be used as carry‐on particles to deliver therapeutic molecules to specific tissues and sites.…”
Section: Circulating Tumor Biomarkersmentioning
confidence: 99%
See 2 more Smart Citations